2018
DOI: 10.1016/j.cej.2017.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of biomass char combustion in a low temperature fluidized bed reactor

Abstract: The purpose of this work is the kinetic study of biomass char combustion in a low temperature fluidized bed reactor. This char was obtained from fast pyrolysis of beech stick in an annex batch fluidized bed reactor at 923 K and atmospheric pressure. Operating conditions of the combustion were thoroughly characterized so that the reaction takes place in isothermal conditions and a constant oxygen partial pressure. The kinetic study was performed for temperatures up to 643 K, oxygen partial pressures ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…As a general rule, polymers with an aliphatic backbone, like PLA, tend to generate less smoke during combustion than polyenic polymers and those with pendant aromatic groups, such as polystyrene, which produce more smoke [ 49 ]. Organic materials produce toxic carbon monoxide (CO) when not completely combusted, and in the later stages of combustion CO is oxidized to CO 2 [ 50 ]. From Table 6 , the addition of BP significantly increased the amounts of CO and CO 2 released from the material, whereas its substitution with BC had very mixed results for CO and CO 2 release.…”
Section: Resultsmentioning
confidence: 99%
“…As a general rule, polymers with an aliphatic backbone, like PLA, tend to generate less smoke during combustion than polyenic polymers and those with pendant aromatic groups, such as polystyrene, which produce more smoke [ 49 ]. Organic materials produce toxic carbon monoxide (CO) when not completely combusted, and in the later stages of combustion CO is oxidized to CO 2 [ 50 ]. From Table 6 , the addition of BP significantly increased the amounts of CO and CO 2 released from the material, whereas its substitution with BC had very mixed results for CO and CO 2 release.…”
Section: Resultsmentioning
confidence: 99%
“…During combustion of organic materials, CO and CO 2 are primary products of the carbon–oxygen reaction. CO is generated first, which reacts with O 2 to form CO 2 [ 29 ]. A study by Du et al, (1991) [ 30 ] demonstrated how the presence of Ca in char particles strongly favours the formation of CO 2 as the substrate combusts; at 390 °C, the Ca content in char particles reduced the CO/CO 2 product ratio from 0.53 to 0.007.…”
Section: Resultsmentioning
confidence: 99%
“…The ring system and random bonding reduce the density of charcoal to 1.0 g/cm 3 , which is significantly lower than that of single-crystal graphite (2.267 g/cm 3 ). The spaces between these bonded LCMs constitute the microporous structures of the charcoal, and during pyrolysis and carbonization, mesopores and macropores develop within the char matrix due to shrinkage [7].…”
mentioning
confidence: 80%
“…At low and high temperatures, oxygen almost completely penetrates the charcoal particle before the onset of significant oxidation. At temperatures < 900 K, the specific surface area of char changes as predicted by random pore models [3]. The reactivity of char under both oxidizing and inert conditions has been studied by thermogravimetric analysis [4,5].…”
mentioning
confidence: 99%